Preparation of maghemite-silica nanocomposites using sol-gel technique - Ang, Bee Chin; Yaacob, Iskandar Idris (Trans Tech Publications, Switzerland, 2010)
Superparamagnetic maghemite nanoparticles were successfully produced using Massart's procedure. Nanocomposites consisting of the synthesized maghemite nanoparticles and silica were produced by dispersing the as-synthesized maghemite nanoparticles into the silica xerogel, which was prepared by sol-gel technique. The system was then heated for 3 days at 140°C. A variety of weight ratios of Fe2O3/SiO2 was investigated. The nanocomposites were characterized using TGA, XRD, TEM and AGM. TGA thermogram showed one significant weight loss at around 250°C. It was caused by dehydration and evaporation of solvent from sol-gel process. XRD showed that the dispersed particles were still maghemite. TEM micrographs showed that the maghemite nanoparticles were in spherical shape and they were homogeneously incorporated in the silica matrix. The values of magnetization at 10kOe applied field were in the range of 1.79emu/g to 9.53emu/g depending of the Fe 2O3/SiO2 ratio. Reduction of average crystallite size of dispersed maghemite particles was observed after encapsulation process. Increasing weight ratio of Fe2O 3/SiO2 caused increase of the average crystallite size of maghemite nanoparticles. © (2010) Trans Tech Publications.